2013
DOI: 10.1084/jem.20120150
|View full text |Cite
|
Sign up to set email alerts
|

Germinal center B cells govern their own fate via antibody feedback

Abstract: High-affinity antibodies reenter germinal centers (GCs) and limit antigen access, thus causing sustained directional evolution in GCs toward higher-affinity antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
339
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(363 citation statements)
references
References 36 publications
22
339
1
1
Order By: Relevance
“…A sign of B-cell function is the formation of germinal centers (GCs) in follicles within the spleen and other lymphoid organs, such as Peyer's patches (Pp) and lymph nodes (LNs) (20). In GCs, B cells proliferate and differentiate to produce higher affinity antibodies and switch isotypes (21,22). We found that KO mice had an increased frequency of IgAexpressing GC B cells in Pp compared with WT controls, as well as a variable but, on average, twofold reduction in IgG1-expressing B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A sign of B-cell function is the formation of germinal centers (GCs) in follicles within the spleen and other lymphoid organs, such as Peyer's patches (Pp) and lymph nodes (LNs) (20). In GCs, B cells proliferate and differentiate to produce higher affinity antibodies and switch isotypes (21,22). We found that KO mice had an increased frequency of IgAexpressing GC B cells in Pp compared with WT controls, as well as a variable but, on average, twofold reduction in IgG1-expressing B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fas is highly expressed on activated B cells, particularly in the germinal center, where it mediates the deletion of autoreactive or unproductive somatic hypermutated B cells (12)(13)(14). Fas, as well as its ligand FasL, play critical roles in B-cell apoptosis.…”
mentioning
confidence: 99%
“…Three different affinity-dependent mechanisms with impact on B cell selection and differentiation were compared: DND, affinity-dependent dynamic increase of the number of B cell divisions; DSH, affinitydependent dynamic downregulation of somatic hypermutation (17); and AFB, Ab feedback onto the GC reaction (21). Although DND and DSH both represent mechanisms on the level of individual interactions between B and T cells, which depend on the previously collected, processed, and presented amount of Ag, AFB represents the idea that Abs generated by the GC output increase B cell competition for Ag by coverage of the Ag presented on FDCs.…”
Section: Resultsmentioning
confidence: 99%
“…The novel modeling framework for GC reactions presented in this article can be considered as a combination of the LEDA model (17) and a dynamic description of generated Abs including Ab feedback (AFB) onto the GC dynamics derived from chemical binding kinetics (21). The combined model was further extended to include dynamic and affinity-dependent number of B cell divisions (DND), and dynamic affinity-dependent somatic hypermutation probability (DSH).…”
Section: General Modeling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation